DOI: 10.22215/etd/2017-11819
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Underpinnings of Freeze Tolerance in the Goldenrod Gall Fly Eurosta Solidaginis and the Goldenrod Gall Moth Epiblema Scudderiana

Abstract: Epigenetic underpinnings of freeze tolerance in the goldenrod gall fly Eurosta solidaginis and the goldenrod gall moth Epiblema scudderiana

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 149 publications
(347 reference statements)
1
4
0
Order By: Relevance
“…Not surprisingly, acetyl-histone levels were depressed for most investigated marks (H3K9ac, H3K14ac, H3K27ac, H4K8ac) following prolonged larval freezing (Figure 3). This is strongly indicative of heterochromatic structures and a suppressed transcriptional state, and aligns with Eurosta epigenetic research during shorter freezing timepoints [50]. MRD-mediated reductions in histone acetyl marks (particularly H3K9ac and H3K23ac) have been observed recently, primarily in animal responses to anoxia [7,51] and during ground squirrel hibernation, both being hypometabolic states [8,52].…”
Section: Freeze Exposure Triggers Reductions In Many Transcriptionall...supporting
confidence: 82%
“…Not surprisingly, acetyl-histone levels were depressed for most investigated marks (H3K9ac, H3K14ac, H3K27ac, H4K8ac) following prolonged larval freezing (Figure 3). This is strongly indicative of heterochromatic structures and a suppressed transcriptional state, and aligns with Eurosta epigenetic research during shorter freezing timepoints [50]. MRD-mediated reductions in histone acetyl marks (particularly H3K9ac and H3K23ac) have been observed recently, primarily in animal responses to anoxia [7,51] and during ground squirrel hibernation, both being hypometabolic states [8,52].…”
Section: Freeze Exposure Triggers Reductions In Many Transcriptionall...supporting
confidence: 82%
“…Organisms respond to changes in environmental temperature by activating stress response mechanisms. Studies suggest that epigenetic enzymes play a vital role in arthropod cold hardiness (70). To the best of our knowledge, this is the first report of the response of DNA methyltransferases of D. silvarum and H. longicornis ticks to cold stress.…”
Section: Discussionmentioning
confidence: 70%
“…The protein expression level was down-regulated after 3 days of cold treatment but was up-regulated with the extension of treatment time for both the Dnmts of D. silvarum and H. longicornis. Similarly, a study observed that cold and subzero temperature exposure in Eurosta solidaginis (goldenrod gall fly) resulted in the upregulation of several DNA methyltransferases (70). The down-regulation and up-regulation due to temperature variations is a confirmation of the thermal plasticity of Dnmt expression which is reflected in the corresponding protein expression.…”
Section: Discussionmentioning
confidence: 87%
“…The role of epigenetic responses to cold stress in animal study systems has been less described, although epigenetic modifications have a strong role in initiating and maintaining animal cold acclimation or coping style strategies. For example, differential expression of dnmt, histone acetyltransferase and demethylation enzymes following freeze treatment in the freeze-tolerant goldenrod gall fly (Eurosta solidaginis) and the goldenrod gall moth (Epiblema scudderiana) suggests epigenetic regulation is an essential mechanism involved in freeze survival strategies (Williamson 2017). Investigating the epigenetic marks associated with key genes involved in these strategies would further prove the role of epigenetics in freeze tolerance in these species.…”
Section: Cold Stress Responsementioning
confidence: 99%